2023
DOI: 10.3390/microorganisms11092362
|View full text |Cite
|
Sign up to set email alerts
|

Kocuria Species Infections in Humans—A Narrative Review

Afroditi Ziogou,
Ilias Giannakodimos,
Alexios Giannakodimos
et al.

Abstract: Kocuria species are catalase-positive and coagulase-negative Gram-positive coccoid bacteria that belong to the family Micrococcaceae, order Actinomycetales, and class Actinobacteria. Even though they may be relatively rare, they have been increasingly reported as the causes of human infections lately. The present study aims to review all published cases of Kocuria spp. infections in humans reporting data on epidemiology, microbiology, antimicrobial susceptibility, antimicrobial treatment, and mortality. A narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Notably, among the 24 genera of microbes presented in drake semen, 8 genera that mainly originated from the environment and cloaca were pathogenic microbes. Achromobacter is a key pathogen causing lung injury ( Veschetti et al, 2022 ; Zhou et al, 2023b ); Aerococcus not only associated with urinary tract and bloodstream infections in human ( Tai et al, 2021 ), but also has been reported to be associated with infectious diarrhea in poultry ( Khafagy et al, 2023 ); and Corynebacterium ( Enurah et al, 2016 ), Enterococcus ( Dolka et al, 2017 ), Kocuria ( Yang et al, 2021 ; Ziogou et al, 2023 ), Pseudomonas ( Pattison et al, 2008 ), Rothia ( Zhang et al, 2022 ), and Staphylococcus infections could affect lots of diseases such as haemorrhagic inflammation of the upper respiratory tract, vertebral abscess, necrotic enteritis, and hepatomegaly ( Szafraniec et al, 2022 ), etc. These results suggest that the negative effects of AI in the duck industry may be due to import the harmful microbes into the reproductive tract of female ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, among the 24 genera of microbes presented in drake semen, 8 genera that mainly originated from the environment and cloaca were pathogenic microbes. Achromobacter is a key pathogen causing lung injury ( Veschetti et al, 2022 ; Zhou et al, 2023b ); Aerococcus not only associated with urinary tract and bloodstream infections in human ( Tai et al, 2021 ), but also has been reported to be associated with infectious diarrhea in poultry ( Khafagy et al, 2023 ); and Corynebacterium ( Enurah et al, 2016 ), Enterococcus ( Dolka et al, 2017 ), Kocuria ( Yang et al, 2021 ; Ziogou et al, 2023 ), Pseudomonas ( Pattison et al, 2008 ), Rothia ( Zhang et al, 2022 ), and Staphylococcus infections could affect lots of diseases such as haemorrhagic inflammation of the upper respiratory tract, vertebral abscess, necrotic enteritis, and hepatomegaly ( Szafraniec et al, 2022 ), etc. These results suggest that the negative effects of AI in the duck industry may be due to import the harmful microbes into the reproductive tract of female ducks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results showed that the genera driving the compositional changes of the cultivable aerobiome were predominantly over-represented in the samples transferred to the high-AQI site compared to the samples maintained at the low-AQI site (eight bacteria and six fungal genera) ( Figure 3 B). Many of these over-represented bacterial and fungal genera encompassed human pathogen species [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]; therefore, changes in their abundance due to pollution may significantly worsen human disease outbreaks. On the other hand, only the bacterial genus Exiguobacterium and the fungal genus Penicillium displayed significantly higher abundances in the maintained than transferred communities, and they both also had the highest relative abundances ( Figure 3 B).…”
Section: Discussionmentioning
confidence: 99%